Another new Cyrtodactylus (Squamata: Gekkonidae) from Phong Nha - Ke Bang National Park, central Truong Son, Vietnam - Heidrich, Astrid; Rösler, Herbert; Thanh, Vu Ngoc; Böhme, Wolfgang; Ziegler, Thomas (Zootaxa, 2007)
A new species of Cyrtodactylus is described from the Truong Son (Annamite mountain range) of Quang Binh Province in central Vietnam. It is characterized by 3–5 transversal dorsal bands between the limb insertions, a neckband reaching the posterior margin of eye, 19–20 irregular longitudinal rows of dorsal tubercles, forelimbs with tubercles, 47–50 longitudinal rows of ventrals at midbody, 9–11 precloacal pores in an angular series in males and 16–27 enlarged precloacal scales in both sexes, 20–23 lamellae below the 4th toe, a segmented tail, and lacking of a distinct ventrolateral fold, a precloacal groove and femoral pores, as well as transversally enlarged subcaudal plates. The new species is known only from the karst forests of Phong Nha - Ke Bang National Park. Preliminary data on its natural history are provided.